Utilização de modelo hidrodinâmico para mapeamento de áreas inundáveis - Santos, Kamila Almeida dos (2015)
The urbanization issues is taking place in Brazilian cities has proved disorganized and thus the floods are becoming a recurring phenomenon. The growth of waterproofing in urban land decreases the amount of infiltrated water in the soil during the rainy season, the rivers might otherwise not conform the water demand in the channels in addition to receive a lot of water runoff In this context the hydrodynamic modeling is an important tool to assess the drainage systems and predict the effects of flooding. This study was applied to the watershed of Ribeirão Anicuns in Goiania, where a considerable part of the basin is in an urban area. Using the hydrodynamic model HECRAS were created various flood scenarios with return periods of 15, 25, 50 and 100 years for the project rainfall; there was aid of a geographic information system, using ArcMap 10.0 to the high-resolution orthophoto city and DEM made from airborne laser scanner, with this material extracted the geometry of the basin. In hydrodynamic modeling crafted the model was run in unsteady flow considering the full Saint Venant equation. In addition to the hydrodynamic modeling was carried out a simulation on the INPE simplified model called HAND, which turned out to be an inexpensive tool, easily accessible and with quality results. With the results obtained (flood hydrograph and flood patches concerning the different return times) flood areas were shown in different scenarios created, and you can compare them. The results showed that the flood spot along the basin have become significantly larger as the return periods grow. In urbanized streams were no major changes than the changes that occurred in streams away from the urban area. Streams that are outside the urbanized area focuses on the alert, they are natural streams and showed that will not support the volume of water resulting from this work.